2012
DOI: 10.1289/ehp.1103529
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evidence of Nonoccupational Asbestos Exposure from Processing Libby Vermiculite in Minneapolis, Minnesota

Abstract: Background: Community exposure to asbestos from contaminated vermiculite ore from Libby, Montana, occurred in many processing sites in the United States, including a densely populated urban residential neighborhood of Minneapolis, Minnesota.Objective: We examined exposed community residents who never worked at the plant or never lived with a plant worker for radiographic evidence of lung changes consistent with asbestos exposure.Methods: We obtained posteroanterior chest radiographs to identify the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The evidence of fibrous amphiboles on car tires and on clothing after recreational activities shows that they can be brought back to family members and thus increase the risk of exposure for other populations besides those directly exposed through outdoor dust emissions. Because health effects may occur even at low levels of exposure to fibrous amphiboles (Alexander et al, 2011;Hillerdal, 1999), our data indicate a potential public health threat in southern Nevada. Any potential future land-use projects should carefully determine the risks to both workers and the regional populations because disturbances to these natural desert surfaces cause increased dust emissions (Goossens et al, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…The evidence of fibrous amphiboles on car tires and on clothing after recreational activities shows that they can be brought back to family members and thus increase the risk of exposure for other populations besides those directly exposed through outdoor dust emissions. Because health effects may occur even at low levels of exposure to fibrous amphiboles (Alexander et al, 2011;Hillerdal, 1999), our data indicate a potential public health threat in southern Nevada. Any potential future land-use projects should carefully determine the risks to both workers and the regional populations because disturbances to these natural desert surfaces cause increased dust emissions (Goossens et al, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…33,34 Lower exposure has also been associated with pleural changes in a more recent study, but there were indicators of potential exposure misclassification. 36,37 A study of spirometry results from a community screening program of Libby residents demonstrated increased odds ratios between parenchymal changes and DPT as well as LPT only based on chest radiographs and restrictive spirometry (FEV 1 /FVC greater than lower limits of normal and FVC less than lower limits of normal). 36,37 A study of spirometry results from a community screening program of Libby residents demonstrated increased odds ratios between parenchymal changes and DPT as well as LPT only based on chest radiographs and restrictive spirometry (FEV 1 /FVC greater than lower limits of normal and FVC less than lower limits of normal).…”
Section: Discussionmentioning
confidence: 99%
“…The most notable recent US example is in Libby, Montana, where significant rates of asbestos-related diseases have been observed among community residents who never worked in the vermiculite mining operations; the vermiculite ore was contaminated with as much as 25% amphibole asbestos. Asbestos-related disease has also been found in communities around industrial plants that produced vermiculite from the Libby ore (2,57). An increase in mesothelioma has been documented in communities with asbestos mining in South Africa (48), Australia (14,27), Italy (31) and Quebec (6).…”
Section: Figurementioning
confidence: 99%